2003
DOI: 10.1034/j.1399-0039.2003.00043.x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic affinities among Mongol ethnic groups and their relationship to Turks

Abstract: The central Asian country Mongolia is home to more than 20 tribes and ethnic groups, some of which are related to neighboring Turkic populations. The main Mongolian people, Khalkha, live in central and eastern Mongolia while the Tsaatan minority lives in the north of the country. The Oold minority is from the western Altai mountain region and live in close proximity with Turkic people. We have typed the HLA-A, -B, -Cw, -DRB1 and -DQB1 loci by PCR-SSP in these three Mongolian populations as well as a sample of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 19 publications
(27 reference statements)
2
33
0
1
Order By: Relevance
“…Machulla et al were typed HLA A, B, CW,DRB1 and DQB1 locuses in mogolian population by PCR-SSP method. [23] They compared results with some societies. Their results were similar to Khalka, Tsactan; but different from Geman and Anatolian Turkish population.…”
Section: Discussionmentioning
confidence: 99%
“…Machulla et al were typed HLA A, B, CW,DRB1 and DQB1 locuses in mogolian population by PCR-SSP method. [23] They compared results with some societies. Their results were similar to Khalka, Tsactan; but different from Geman and Anatolian Turkish population.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these samples from our previous newborn study (origin: South Wales, UK) 42 carried B*0801-DRB1*0301, B*1302-DRB1*0701 and B*4402-DRB1*0401, respectively; two samples from bone marrow donors from the Korea Marrow Donor Program (KMDP) 112 carried B*3701-DRB1*1001; two samples from a Mongolian population study 113 carried B*5801-DRB1*0301; and two samples from a Zambian HIV-1 transmission study 114 carried B*4201-DRB1*0302. All had the same HLA and non-HLA gene polymorphisms as the corresponding CEHs.…”
Section: Other Samplesmentioning
confidence: 99%
“…[7][8][9] It is notable that A*24 is present with the highest frequency in all the tribal communities and North Indian population, but not in the other world populations. [7][8][9] A*31 has been reported to be the most frequent allele in the Dravidian caste groups of South India (TamilNadu), [20] however in the present study it was present only at a lower frequency in the RND group and mostly absent among the tribals. This shows that there might be considerable difference between the genetic make-up of Dravidian communities in TamilNadu and Kerala.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5] Several investigators have used the HLA system to understand human genetic relatedness and migrations of different world populations. [4,[6][7][8][9] In an earlier study we have reported the HLA -B and -C polymorphism in various tribal communities of South India. [10] In the present study, we have analyzed the HLA-A allele frequency and HLA class I haplotypes in seven tribal populations of Kerala and one non-tribal population.…”
mentioning
confidence: 99%